ANALISIS HARGA POKOK PRODUKSI PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) MAKANAN RINGAN DESA BUGO JEPARA - Rosidah; Candra Sigalingging (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
In Bugo Village, Jepara, an UMKM snack company makes a variety of loaves and cakes, such as moho bread and peanuts cakes. At present, small and medium-sized micro-food snack business (UMKM) in Bugo Village, Jepara has set the selling price of products based on market prices. However, further analysis of the production price of raw materials from the cost structure of production has not been carried out by UMKM snacks Village Bugo, Jepara. As a result, they do not have the ability to evaluate the financial performance of the business that they have been doing all this time. The purpose of this research is to analyze the cost structure of production at UMKM that produces snacks in Bugo Village, Jepara. In addition, this research will evaluate the financial performance of the enterprise, i.e. the profits earned by that enterprise. The research uses information from UMKM snack owners in Bugo Village, Jepara and their observations. The total production cost of Rs.1,173,000 consists of raw material costs, direct labour costs, overhead factory costs using the full costing method. If they use the selling price of the current market product, they still get a profit.